Longitudinal functional outcomes and late effects of radiation following treatment of nasopharyngeal carcinoma: secondary analysis of a prospective cohort study - Gia Gill; Ciaran Lane; Candace Myers; Evan D. Kerr; Pascal Lambert; Andrew Cooke; Paul D. Kerr (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The study objectives were: provide longitudinal data on upper aerodigestive tract function and late complications following IMRT for nasopharyngeal carcinoma, and elucidate factors that might predict a worse outcome. The hypotheses were: (1) Despite advances such as IMRT, radiation will cause significant functional decline and late complications that often progress or arise years after treatment. (2) Larger radiation volume will be associated with poorer outcomes. Methods Longitudinal, observational cohort study of nasopharyngeal carcinoma patients with retrospective analysis of prospectively collected, population-based data. Late sequelae and validated measures of overall performance, speech, and swallowing were documented pre-treatment and 3,6,12, 24, 36 and ≥ 60-months post-treatment. Results Forty-two patients treated curatively with radiation (N = 9) or chemoradiation (N = 33) were followed for a median 74 months. Functional outcomes showed an initial nadir at 3 months associated with acute effects of treatment, followed by initial recovery. There was subsequent functional decline years post-treatment with advancing dysphagia/aspiration, trismus, muscle spasm, and hypoglossal nerve palsy. Univariable regression analysis revealed that increasing high-dose radiation volumes (PTV 70 Gy) were associated with increased likelihood of less than solid diet (Performance Status Scale (PSS)—Normalcy of Diet score < 50; p = 0.04), and reduced PSS—Understandability of Speech (p = 0.005). The probability of poor outcome increased with time. Eleven percent of patients were tube feed dependent at ≥ 5 years. Conclusions Despite improvements in radiation delivery, late effects of radiation remain common. Higher radiation volumes are associated with poorer outcomes that worsen over time. Graphical Abstract